Improving mental health among intensive care unit staff with communication skills training - Holmberg, Johan; Rosendahl, Ingvar; Andersson, Rebecca; Kemani, Mike K.; Holmström, Linda; Öst, Lars-Göran; Wicksell, Rikard K. (Frontiers in Psychology, 2024)
Purpose Intensive Care Unit (ICU) staff report that a large part of the work-related distress they experience is related to communication situations with colleagues, patients, and relatives. Based on these findings, the aim of the present study was to preliminary evaluate the effects of a novel Communication Skills Training (CST) program on mental health among ICU staff. Methods The CST program was delivered to the entire work force of an ICU at a Swedish hospital and was evaluated as an uncontrolled clinical trial with three repeated measures. 100 participants were eligible and included in the analyses. The theoretical framework for the program was learning theory and cognitive behavioral therapy. The program was delivered by two psychologists and included one full-day lecture and three subsequent two-hour supervision sessions. Changes in mental health was evaluated with self-report questionnaires measuring perceived stress, general mental health, work engagement, and psychological flexibility. Results Analyses of three repeated measures showed significant improvements with 1.3 points lower perceived stress and 2.0 points lower general mental health after the intervention. No differences were seen in measures of work engagement or psychological flexibility. Conclusion Findings of the study supports the utility of the CST program as an intervention to target perceived stress and general mental health within intensive care. These findings should be further validated in trials with improved design.